Identifikasi Bakteri Patogen Sungai Bedadung di Jember Indonesia (Identification of Bedadung River Pathogen Bacteria in Jember, Indonesia) - Enny Suswati; Dini Agustina; Rini Riyanti; Muhammad Ali Shodikin; Elly Nurus Sakinah; Desi Sandra Sari; Yuliana MDA; Ema Rachmawati (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2024)
The Bedadung River is a typical environment where anthropogenic pollution often occurs thus rapidly changing the chemical and biological composition of the sediments and surface water. However, the effects of urbanization on the organization and diversity of the microbial community in rivers have not been adequately studied. A thorough examination of the microbial dispersion in the Bedadung River's surface water is presented. This research aims to determine the type and prevalence of pathogenic bacteria from Bedadung River water samples, Jember Regency. To investigate the prevalence of bacterial contaminants, sixteen sites along the Bedadung River were chosen. Bacterial isolation and identification using chromogenic media, such as Salmonella Chromogenic Agar (SCA) and Mannitol Salt Agar (MSA). Using API E 20 media, the bacteria were identified based on the color of the bacterial colonies in growth. The results indicated that contaminant bacteria isolated from Bedadung River water in Jember were S. aureus (96.67%), E. coli (98.33%), Salmonella sp. (96.67%), Shigella sp. (40%), and Proteus sp. (1.67%). These findings indicate that the river was a significant source of bacteria with a risk potential to humans and the environment that must be addressed. Many actions are needed to reduce fecal contamination of river water.